Procalcitonin Levels in Pulmonary Tuberculosis and Bacterial Pneumonia: A Cross-Sectional Study at a Tertiary Hospital in Indonesia - Abdullah Fikri; Hadi Nugraha Mustofa; Zen Ahmad; Zen Hafy (HM Publisher, 2025)
Background: Pulmonary tuberculosis (TB) and bacterial pneumonia are respiratory infections with high morbidity and mortality rates. Despite having similar clinical symptoms and radiological findings, these conditions require different treatment approaches. Procalcitonin is a potential biomarker to differentiate these conditions, as its levels tend to increase in bacterial infections but not in TB. This study aims to compare procalcitonin levels in patients with pulmonary TB and bacterial pneumonia. Methods: This research employed an observational analytic design with a cross-sectional approach conducted at Dr. Mohammad Hoesin General Hospital (RSMH), Palembang. The study subjects were patients with pulmonary TB and bacterial pneumonia who met the inclusion and exclusion criteria. Procalcitonin levels were measured using ELISA methods. Data were analyzed to determine differences in procalcitonin levels between the two groups. Results: The study found that procalcitonin levels in bacterial pneumonia patients were significantly higher than those in pulmonary TB patients (p<0.05). These findings indicate that procalcitonin levels can serve as a diagnostic parameter to distinguish between the two conditions. Conclusion: Procalcitonin levels can be a useful biomarker for differentiating pulmonary TB from bacterial pneumonia. This biomarker is expected to assist clinicians in making more accurate diagnoses and expediting clinical decision-making.